A method for preparing high-performance catalyst using chromium ion pollutants in surface water
By treating nickel foam into nickel-iron layered double hydroxide array material and performing electrolytic water reaction in surface water, the problems of non-recyclable utilization and low economic value of metal ion pollution treatment in the prior art are solved, and the effect of efficient adsorption of chromium ions and improving catalyst performance is achieved.
Patent Information
- Application Number
- CN202211643240.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-12-20
AI Technical Summary
The prior art has problems such as non-recycling, consumption of other materials and its own pollution when dealing with metal ion pollution, and its economic value is low. Although electrochemical adsorption of metal ions is effective, it consumes a lot of electricity and has no economic value for by-products.
By cutting the foam nickel foam and processing it in hydrochloric acid and ferric nitrate solutions, a nickel-iron layered double hydroxide array material is generated as working electrodes and catalysts, and an electrolytic reaction is carried out in surface water containing chromium ions, adsorbing and modifying chromium ions, improving the structure and electron state of the catalyst.
The preparation of high-performance catalysts is realized, which can effectively adsorb chromium ions in surface water, reduce pollution, and improve the performance and energy conversion efficiency of the catalyst.
Smart Images

Figure CN115948762B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new energy materials and metal ion pollution treatment, and in particular to a method for preparing a high-performance catalyst by utilizing chromium ion pollutants in surface water. Background Art
[0002] Under the requirements of the green and environmentally friendly development concept, water pollution control has become an important issue that people are concerned about today. Among them, metal ion pollution is an important issue that needs to be solved urgently. Scientific research shows that the presence of metal ions in water cannot be naturally degraded, which will cause serious damage to water quality and affect the growth of plants and animals in the water. When water containing excessive metal ions is ingested by the human body, it will cause irreparable damage to the human body.
[0003] At present, common methods for treating metal ions include chemical precipitation, redox treatment and solvent extraction. Existing methods are generally non-recyclable, require the consumption of other materials, have certain pollution problems, and have low economic value. Using electrochemical method to adsorb metal ions is an effective method. Through electrochemical adsorption, metal ions in water can be continuously absorbed, and through appropriate design, the generated by-products have extremely high economic value.
[0004] The common method of treating metal ions in the market now is to use other substances to form adsorption or co-precipitation substances, and the by-products have no economic value. In the related research on the electrochemical absorption of metal ions, because the catalytic material has unique structural characteristics, the metal ions will be adsorbed on the surface of the electrode material under the action of the electric potential. The common electrophoresis method for adsorbing metal ions consumes a lot of electricity, and the amount of adsorption is limited.
[0005] In the prior art, there is a method for preparing a nickel foam loaded TiO2 photocatalyst (CN201410523732.9), which comprises the following steps: preparing a wet gel formed by nano-TiO2 by a sol-gel method, drying it at 60°C, calcining the obtained dry gel at 400°C for 3h, cooling it with the furnace, and preparing TiO2 powder, dissolving the TiO2 powder in deionized water, dispersing it by ultrasonic oscillation for about 20min, and then depositing the TiO2 powder on a carrier nickel net by an electrophoretic deposition method, sintering it at a certain temperature, and obtaining a nickel foam loaded TiO2 photocatalyst. The preparation process of this scheme is complicated, requires high temperature, ultrasonic and other conditions, takes a long time, and consumes high costs in production. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a high-performance catalyst using chromium ion pollutants in surface water, which combines water electrolysis and metal ion adsorption, and completes two reaction processes simultaneously using only the energy required for electrolysis. While electrolyzing water, the problem of metal ion pollution in the water body is solved; at the same time, the adsorbed metal ion chromium will further improve the electronic structure of the catalyst, optimize the catalytic performance of the material, further expand the energy conversion efficiency, and increase the oxygen production.
[0007] To achieve the above object, the present invention provides a method for preparing a high-performance catalyst using chromium ion pollutants in surface water, comprising the following steps:
[0008] S1, cutting the nickel foam into small pieces of 1×0.2 cm to 2×2 cm, then soaking the nickel foam in a 1-6M hydrochloric acid solution for 3-30 minutes, taking out the nickel foam, and rinsing with anhydrous ethanol;
[0009] S2, soaking the nickel foam washed with acid in the step S1 in a 0.5-10M ferric nitrate solution for 2-10 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material;
[0010] S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 0.01M to 1M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will be adsorbed on the catalyst material to play a modifying role.
[0011] Preferably, the method comprises the following steps:
[0012] S1, cutting the nickel foam into small pieces of 1×0.2 cm, then soaking the nickel foam in a 1M hydrochloric acid solution for 30 minutes, taking out the nickel foam, and rinsing with anhydrous ethanol;
[0013] S2, soaking the nickel foam washed with acid in step S1 in a 1M ferric nitrate solution for 2 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material;
[0014] S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 0.01M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
[0015] Preferably, the method comprises the following steps:
[0016] S1, cutting the nickel foam into small pieces of 2×2 cm, then soaking the nickel foam in a 6M hydrochloric acid solution for 3 minutes, taking out the nickel foam, and rinsing with anhydrous ethanol;
[0017] S2, soaking the nickel foam washed with acid in the step S1 in a 0.2M ferric nitrate solution for 10 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material;
[0018] S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 0.1M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
[0019] Preferably, the method comprises the following steps:
[0020] S1, cutting the nickel foam into small pieces of 1×1.5 cm, then soaking the nickel foam in a 3M hydrochloric acid solution for 5 minutes, then taking out the nickel foam and rinsing it with anhydrous ethanol;
[0021] S2, soaking the nickel foam washed with acid in the step S1 in a 0.5M ferric nitrate solution for 5 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material;
[0022] S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 1M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
[0023] Preferably, the concentration of the ferric nitrate solution does not exceed 10 M to prevent the nickel foam that has been pickled in step S1 from being severely corroded.
[0024] Therefore, the present invention adopts the above-mentioned method for preparing a high-performance catalyst using chromium ion pollutants in surface water, and the regulating effects of acid washing and ferric nitrate improve the structure and electronic state of the catalyst, thereby generating a high-performance catalyst for oxygen evolution reaction in electrolyzed water; the unique structure and electronic state of the catalyst are more conducive to the adsorption of metal ions in surface water, and can achieve the effect of simultaneously adsorbing metal ions to reduce pollution and improve catalyst performance.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is a performance test diagram of the nickel-iron layered double hydroxide prepared in Example 1 of the method for preparing a high-performance catalyst using chromium ion pollutants in surface water of the present invention in different solutions;
[0027] Figure 2 The LSV curve diagram of the stability test of the nickel-iron layered double hydroxide prepared in Example 1 of the method for preparing a high-performance catalyst by utilizing chromium ion pollutants in surface water of the present invention in an alkaline solution prepared from surface water;
[0028] Figure 3 This is an XPS graph of nickel-iron layered double hydroxide before and after stability test of Example 1 of a method for preparing a high-performance catalyst using chromium ion pollutants in surface water according to the present invention;
[0029] Figure 4 This is a SEM image of the nickel-iron layered double hydroxide prepared in Example 1 of the method for preparing a high-performance catalyst using chromium ion pollutants in surface water of the present invention before electrolysis testing;
[0030] Figure 5 This is a SEM image of the nickel-iron layered double hydroxide prepared in Example 1 of the method for preparing a high-performance catalyst using chromium ion pollutants in surface water after electrolysis testing. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0032] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0033] Embodiment 1
[0034] S1, cutting the nickel foam into small pieces of 1×1.5 cm, then soaking the nickel foam in a 3M hydrochloric acid solution for 5 minutes, then taking out the nickel foam and rinsing it with anhydrous ethanol;
[0035] S2, soaking the nickel foam washed with acid in the step S1 in a 0.5M ferric nitrate solution for 5 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material;
[0036] S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 1M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
[0037] Embodiment 2
[0038] S1, cutting the nickel foam into small pieces of 1×0.2 cm, then soaking the nickel foam in a 1M hydrochloric acid solution for 30 minutes, taking out the nickel foam, and rinsing with anhydrous ethanol;
[0039] S2, soaking the nickel foam washed with acid in step S1 in a 1M ferric nitrate solution for 2 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material;
[0040] S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 0.01M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
[0041] Embodiment 3
[0042] S1, cutting the nickel foam into small pieces of 2×2 cm, then soaking the nickel foam in a 6M hydrochloric acid solution for 3 minutes, taking out the nickel foam, and rinsing with anhydrous ethanol;
[0043] S2, soaking the nickel foam washed with acid in the step S1 in a 0.2M ferric nitrate solution for 10 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material;
[0044] S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 0.1M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
[0045] Experimental testing
[0046] The nickel-iron layered double hydroxide array material prepared in Example 1 was selected for performance testing, and the performance testing process included:
[0047] 1. Prepare 1M NaOH solution;
[0048] 2. Rinse the platinum electrode, reference electrode and electrode clamp required for the test with deionized water, then place the platinum electrode and reference electrode, and clamp and place the prepared nickel-iron layered double hydroxide array material with the electrode clamp;
[0049] 3. Turn on the electrochemical workstation test instrument and place the corresponding working electrode;
[0050] 4. Fix the electrode according to the area of the nickel-iron layered double hydroxide array material immersed in the solution (about 0.8 square centimeters);
[0051] 5. Use computer operation to pass current test to draw the LSV curve of nickel-iron layered double hydroxide array material.
[0052] (I) Activity test
[0053] like Figure 1 As shown, the activity test results of the nickel-iron layered double hydroxide array material prepared in Example 1 in 1M NaOH prepared from deionized water and 1M NaOH prepared from surface water, respectively. Surface water mainly refers to surface water containing chromium ion pollutants formed in the subsidence area of the mining area. The experimental conditions for testing the nickel-iron layered double hydroxide array material in 1M NaOH prepared from deionized water and 1M NaOH prepared from surface water are set to be the same.
[0054] (II) Stability test
[0055] like Figure 2 , which is an LSV curve of the stability test of the nickel-iron layered double hydroxide array material prepared in Example 1 in a 1M NaOH solution prepared from surface water. Figure 3 is the XPS graph of the nickel-iron layered double hydroxide array material before and after the stability test, and Table 1 is the chromium content in the surface water before and after the stability test.
[0056] The stability test was performed using an electrochemical workstation with a three-electrode test system and a fixed voltage chronoamperometry method.
[0057] Table 1 Chromium content in surface water before and after stability test
[0058]
[0059] (III) The nickel-iron layered double hydroxide array material prepared in Example 1 was subjected to an oxygen evolution half-reaction test for hydrogen production by electrolysis of water in a 1M NaOH solution prepared from surface water containing chromium ions. Figure 4 The figure shows the SEM image of the nickel-iron layered double hydroxide array before the electrolysis test. Figure 5 This is the SEM image of the nickel-iron layered double hydroxide array after electrolysis test.
[0060] In the present invention, the nickel foam is pickled to remove the impurity ions on the surface of the nickel foam, and then washed with anhydrous ethanol; the nickel foam after pickling is immersed in a ferric nitrate solution, and the iron ions are attached and precipitated on the surface of the nickel foam to generate a nickel-iron layered double hydroxide array material, and the concentration of the ferric nitrate does not exceed 10M to prevent the nickel foam from being seriously corroded; the synthesized nickel-iron layered double hydroxide array is used as an electrode and a catalyst and placed in an alkaline solution prepared from surface water, and metal ion pollutants such as chromium ions can be adsorbed therein, so as to modify the nickel-iron double hydroxide array, facilitate the oxygen evolution half reaction of hydrogen production by electrolysis of water, and improve its activity and stability at the same time.
[0061] Therefore, the present invention adopts the above-mentioned method for preparing a high-performance catalyst using chromium ion pollutants in surface water, and improves the structure and electronic state of the catalyst by adsorbing and precipitating the chromium ion pollutants in the water, thereby generating a high-performance catalyst for the electrolytic water oxygen evolution reaction; the unique structure and electronic state of the catalyst are more conducive to the adsorption of chromium metal ions in surface water, and can achieve the effect of simultaneously adsorbing chromium metal ions to remove pollutants and improving catalyst performance.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-performance catalyst using chromium ion pollutants in surface water, characterized in that: The steps include: S1, cutting the nickel foam into small pieces of 1×0.2 cm~2×2 cm, then soaking the nickel foam in a 1~6M hydrochloric acid solution for 3~30 minutes, taking out the nickel foam, and rinsing with anhydrous ethanol; S2, soaking the nickel foam washed with acid in the step S1 in a 0.5-10M ferric nitrate solution for 2-10 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material; S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 0.01M~1M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will be adsorbed on the catalyst material, playing a modifying role.
2. The method for preparing a high-performance catalyst using chromium ion pollutants in surface water according to claim 1, characterized in that: The steps include: S1, cutting the nickel foam into small pieces of 1×0.2 cm, then soaking the nickel foam in a 1M hydrochloric acid solution for 30 minutes, taking out the nickel foam, and rinsing with anhydrous ethanol; S2, soaking the nickel foam washed with acid in step S1 in a 1M ferric nitrate solution for 2 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material; S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 0.01M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
3. The method for preparing a high-performance catalyst using chromium ion pollutants in surface water according to claim 1, characterized in that: The steps include: S1, cutting the nickel foam into small pieces of 1×1.5 cm, then soaking the nickel foam in a 3M hydrochloric acid solution for 5 minutes, then taking out the nickel foam and rinsing it with anhydrous ethanol; S2, soaking the nickel foam washed with acid in the step S1 in a 0.5M ferric nitrate solution for 5 minutes, then taking it out and drying it at 60° C. to obtain a nickel-iron layered double hydroxide array material; S3. Using the nickel-iron layered double hydroxide array material obtained in step S2 as a working electrode and catalyst, electrolyzing water in a 1M NaOH solution prepared with surface water containing chromium ions, during the electrolysis process, the chromium ions in the solution will continue to be adsorbed on the catalyst.
4. The method for preparing a high-performance catalyst using chromium ion pollutants in surface water according to claim 1, characterized in that: The concentration of the ferric nitrate solution does not exceed 10M to prevent the nickel foam that has been pickled in step S1 from being severely corroded.
Citation Information
Patent Citations
Preparation method of foamed nickel-supported TiO2 photocatalyst
CN104307525A
Chromium oxide functionalized ferronickel hydrotalcite nanosheet as well as preparation method and electro-catalysis application thereof
CN115305481A